SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS OF PROFESSIONAL POLICING CONFLICTOLOGY - Лефтеров, В.; Яковлев, Д. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article deals with the problems of conflict in police work as a part of police psychology. Scientific methodological and structural components of scientifically applied industry and discipline "Professional Police Conflictology" are systematized. This discipline is suggested to include into professional training for the National Police of Ukraine. Key words: conflictology, police psychology, professional police conflictology, police officers, conflicts.